All Days 2011
DOI: 10.4043/21212-ms
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Nanoparticles as Harsh-Condition Emulsion and Foam Stabilizers and as Novel Sensors

Abstract: Nanoparticles, when synthesized in a specific size range and with a special surface coating tailored to achieve certain desired functionalities, exhibit unique properties. This is because they are almost of molecular size but still retain many useful colloidal characteristics. Recent developments on novel potential upstream applications of nanoparticles are reviewed with focus on research at our laboratory. Oil-water emulsions and CO2 foams that have long-term stability under harsh downhole conditions could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…With the desired size, shape, and surface properties, NPs can make very stable suspension in water, oil, or other polymer-based fluids that can endure harsh reservoir temperature and pressure conditions (Zhang et al, 2011). Also these NPs found to be compatible with reservoir fluids and environmental friendly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the desired size, shape, and surface properties, NPs can make very stable suspension in water, oil, or other polymer-based fluids that can endure harsh reservoir temperature and pressure conditions (Zhang et al, 2011). Also these NPs found to be compatible with reservoir fluids and environmental friendly.…”
Section: Introductionmentioning
confidence: 99%
“…Also these NPs found to be compatible with reservoir fluids and environmental friendly. Zhang et al (2011) reported very stable oil in water and water-in-oil emulsion in the presence of different silica NPs. These emulsions also remain stable in reservoirs harsh conditions due to the irreversible adsorption on their droplet surface.…”
Section: Introductionmentioning
confidence: 99%
“…Kanj et al [5] identified the usable size of nanoparticles in reservoir rocks through nano-fluid core flooding experiments. Using hydrophilic/hydrophobic synthesized nanoparticles, Zhang [6] made oil in water emulsions and stabilized CO 2 foams with quite high stability.…”
Section: Introductionmentioning
confidence: 99%
“…Kanj et al [5] identified the usable size of nanoparticles in reservoir rocks through nanofluid core flooding experiments. Using hydrophilic/hydrophobic synthesized nanoparticles, Zhang [6] made oil in water emulsions and stabilized CO 2 foams with quite high stability.…”
Section: Introductionmentioning
confidence: 99%